Effectiveness of long-distance training using kirkpatrick evaluation - Rahmadani (12 Waiheru, 2022)
Distance training is one of the training models carried out at the Ambon Religious Education and Training Center or Balai Diklat Keagamaan Ambon (BDK) as a solution to facing the current pandemic era. To determine the effectiveness of Distance training, a training evaluation was conducted. One form of evaluation that is appropriate to measure the effectiveness of training is the Kirkpatrick model which includes four levels, namely: level 1 reaction, level 2 learning, level 3 behavior, and level 4 result. In this article, an evaluation was conducted regarding Distance Training at BDK Ambon using Kirkpatrick’s Model level 1 and level 2. The study was conducted on Madrasah teachers who attended Distance Training at the Ambon Religious Education Center. The results showed that in level 1, namely reaction, the satisfaction of distance training participants was quite effective because the survey results showed the average score was 89.47. It means that in the training process, participants feel comfortable and satisfied. Participants are also able to be motivated in attending lessons and training. Meanwhile, for level 2, namely learning, it shows the average value of the participants' learning outcomes is 82.97 which means satisfactory. This is also supported by the results of an interview conducted with one of the lecturers who taught the training. He said that the participants were quite enthusiastic about participating in the training. In addition, the participants 'understanding was also quite good, especially since most of the participants were young teachers who were quite knowledgeable about technology so the assessment of the competency skills of the participants' attitudes, knowledge, and skills was very significant. Thus, distance training conducted at the Ambon Religious Education and Training Center is quite effective. In the future, it is necessary to evaluate other training and education as a reference for the institution.